2003
DOI: 10.1002/adsc.200303098
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Chloride‐Catalyzed Addition Reactions of Electron‐Rich Arenes to Methyl Vinyl Ketone

Abstract: For the reaction of a,b-unsaturated ketones with electron-rich arenes catalyzed by gold(III) chloride both, a Friedel±Crafts-type mechanism and an initial metallation, are evaluated. Gold(III) chloride has proven to be an efficient catalyst under very moderate reaction conditions, however, in the case of sterically demanding products HBF 4 turned out to be the superior catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(50 citation statements)
references
References 32 publications
0
49
0
1
Order By: Relevance
“…In analogy to our recent report, [8] the conversions leading to 12, 14 and 16 can also be conducted with Brønsted acids with non-nucleophilic counterions.…”
mentioning
confidence: 87%
“…In analogy to our recent report, [8] the conversions leading to 12, 14 and 16 can also be conducted with Brønsted acids with non-nucleophilic counterions.…”
mentioning
confidence: 87%
“…[12] From a mechanistic point of view, the activation of the electrophilic species by coordination of the LA is widely accepted to be the key step of the process. [13] However, there is an alternative reaction pathway that has been extensively investigated, proved, and exploited in the cycloalkenylation of arenes, namely C-H activation by a metal. [4,14] Since the initial electrophilic mercuriation discovered over one century ago, [15] many transition metals such as Pt, Au, Pd, and Rh have proved their effectiveness in promoting electrophilic aromatic metalations.…”
Section: Catalytic Intramolecular Processesmentioning
confidence: 99%
“…The Au(I) complexes Et 3 PAuCl and (THT)AuCl (where THT is tetrahydrothiophene) also catalyse the reaction, albeit less effectively and only in the presence of AgBF 4 (80-90%, 1 mol% catalyst, 1 day). [17] It is unclear how the AgBF 4 enhanced the catalytic activity in this case; however, oxidation of Au(I) to Au(III) by the silver cannot be excluded. Aguilar et al subsequently investigated a series of less acidic, air-and moisture-stable C,Nand N,N -cyclometallated gold(III) complexes as catalysts in the reaction, [18,19] and observed that the catalytic activity of neutral C,N-cycloaurated complexes was greatly enhanced by added silver salts.…”
Section: Introductionmentioning
confidence: 98%